Practicing COVID-19 Public Health Measures Is Associated With Anxiety and Depression in Undergraduate University Students - Kelley Holladay; David Lardier; Fabiano T. Amorim; Micah Zuhl; Kathryn E. Coakley (Frontiers Media S.A., 2022)
BackgroundCOVID-19 has affected mental health globally, increasing depression and anxiety. This study examined relationships between practicing COVID-19-related public health measures and depression and anxiety in young adult students.MethodsA sample of 755 undergraduate students 18-25 years of age at a large public university completed a cross-sectional survey in fall 2020 during the pandemic (response rate = 18.9%). The survey included demographic questions, anxiety and depression screeners (GAD-7 and PHQ-9), and questions on practicing public health measures (stay-at-home orders, quarantining, social distancing, etc.) since March 2020. Multivariate logistic regression was utilized to calculated adjusted odds between practicing public health measures and anxiety and depression.ResultsThe majority of respondents reported practicing public health measures; however, 53% experienced anxiety (GAD-7 score >10) and 57% experienced depression (PHQ-9 score >10) in the 2 weeks prior to completing the survey. Participants who quarantined had significantly higher odds of anxiety (AOR = 1.44; 95% CL 1.07, 1.96) and depression (AOR = 1.77; 95% CL 1.30, 2.41) than those who did not. Participants who self-isolated also had significantly higher odds of anxiety (AOR = 1.53; 95% CL 1.13, 2.08) and depression (AOR = 1.87; 95% CL 1.37, 2.56) compared to those who did not. Moving/changing living situations in response to the pandemic also increased odds of depression (AOR = 1.86; 95% CL 1.33, 2.60).ConclusionYoung adult undergraduate students experienced a high prevalence of anxiety and depression. Quarantining, self-isolating, and moving/changing living situations increased odds of anxiety and/or depression. The public health measures necessary for COVID-19 control and prevention may adversely affect mental health.